ESTIMATING CAUSAL EFFECTS OF ALCOHOL ACCESS AND USE ON A BROAD SET OF RISKY BEHAVIORS: REGRESSION DISCONTINUITY EVIDENCE. (5th September 2018) - Fletcher, Jason M.
Abstract : A growing body of evidence suggests large increases in criminal behavior and mortality coinciding with a young adult's 21st birthday, when alcohol consumption becomes legal. The policy implications from these findings have focused on the need to reduce drinking among young people, potentially by enforcing stricter alcohol controls. However, mortality and arrests are relatively infrequent outcomes and relatively less is known about the intermediate and more prevalent consequences of legal access to alcohol at age 21. This paper uses the Add Health data combined with a regression discontinuity approach to examine the effects of alcohol access on sexual behavior, drunk driving, violence, and other outcomes. The results suggest relatively large effects that appear concentrated in men. The sample also allows some suggestive policy implications on whether changing the minimum drinking age may reduce these consequences. ( JEL I12, I18)